PERSUASIVE MESSAGE CONSTRUCTION IN SPAYLATER ADVERTISEMENTS ON SHOPEE INDONESIA’S YOUTUBE ACCOUNT - Zaidan Abiyyu Ro'in, Muhammad; Mustika Chairil, Augustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Persuasive communication has become one of the main strategies used in digital advertising, particularly in promoting Buy Now Pay Later (BNPL) services through social media platforms. This study aims to analyze the construction of persuasive messages in SPayLater advertisements on Shopee Indonesia’s YouTube account. The research employed a qualitative descriptive method using Klaus Krippendorff’s content analysis approach. The object of this study consisted of seven SPayLater advertisement contents published between December 2024 and December 2025. Data were collected through observation and documentation techniques by analyzing narration, dialogue, slogans, visual displays, and persuasive elements contained in the advertisements. The findings reveal that SPayLater advertisements predominantly applied one-sided messages, anticlimax structures, and explicit conclusions to encourage immediate audience action. In terms of language style, the advertisements consistently used simple, concise, and repetitive persuasive language to strengthen audience understanding and message recall. Furthermore, reward appeals and motivational appeals were identified as the dominant persuasive strategies, while fear appeals were absent from the advertisements. The advertisements emphasized promotional benefits such as cashback, discounts, free shipping, and installment flexibility to create positive audience perceptions toward BNPL services. These findings indicate that SPayLater advertisements function not only as promotional media, but also as persuasive communication tools that normalize installment-based consumption within contemporary digital culture. This study contributes to digital communication research by providing a systematic analysis of persuasive message construction in BNPL advertising content on social media platforms.